The godfather. Part II [videorecording (Blu-Ray)] - Coppola, Francis Ford, 1939-; Coppola, Francis Ford, 1939-; Coppola, Francis Ford, 1939-; Pacino, Al, 1940-; Duvall, Robert; Keaton, Diane; Shire, Talia; De Niro, Robert; Cazale, John, 1936-1978; Kirby, Bruno, 1949-2006; Puzo, Mario, 1920-1999 (Paramount, 2017)
Continues the saga of the Corleone family, tracing the rise of Don Vito as a young man in Italy, and that of Michael as the new Don, reigning from his Lake Tahoe estate.